Der Lima-Text als Maßstab heutiger Taufinterpretation und Taufpraxis - Brand, Eugene L. (Jahrbuch für Liturgik und Hymnologie, 1985)
"It is our great sin that in practice and teaching we have trivialized Baptism! Just regaining a new sense of the momentous step Baptism is both for the person baptized and for the baptizing Church would be a great gain indeed." These two final sentences might be characteristic for the intentions of a lecture which gave Eugene L. Brand of The Lima Text as a Standard for Current Understandings and Practice of Baptism (Congress of Societas Liturgica Boston/Mass. 1985). Regarding Baptism primarily in an eschatological perspective he examines the ecumenical document by essential theological transversals, the pneumatological, the sacramental, the ecclesiological and the ethical one. These four aspects reveal remarkable results concerning the different initiation rites of the Churches, the pedobaptists' and the believer-baptists' traditions, Baptism and membership of the baptized in the one holy catholic and apostolic Church and, last not least, the ethical implications of Baptism. The author's conclusion is, that the Lima text can be a "significant standard for current understandings and practice of Baptism. Though it can be accused of failure to address 'East-West' baptismal problems, though it has scarcely recognized the cultural 'North-South' problems, and though it may be the 'least mature' of the three sections of Lima, the document represents a tremendous step forward."